Non-oriented electrical steel sheet

JP7640926B2Active Publication Date: 2025-03-06NIPPON STEEL CORPORATION
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
JP2024531672
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2023-01-10
Filing Date
2024-01-09
Publication Date
2025-03-06
Estimated Expiration
2044-01-09

AI Technical Summary

Benefits of technology

【0008】 本開示の上記態様によれば、圧延性が問題とならないように、Mnを抑制するとともに、Mn、CuおよびNiなどの元素の含有量を適正化した化学組成とした鋼板において、板面内異方性が小さく全周平均(全方向平均)が優れた磁気特性を得ることができる無方向性電磁鋼板を提供できる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007640926000009
    Figure 0007640926000009
  • Figure 0007640926000001
    Figure 0007640926000001
  • Figure 0007640926000002
    Figure 0007640926000002
Patent Text Reader

Abstract

Provided is a non-oriented electromagnetic steel sheet comprising, in terms of mass%, not more than 0.0100% of C, 1.50-4.00% of Si, 0.0001-1.0% of sol. Al, not more than 0.0100% of S, not more than 0.0100% of N, not less than 0.10% of Mn, and a total of less than 2.50% of one or more elements selected from among Mn, Ni, and Cu, wherein the transformation temperature Ar3(°C) is 750-1050°C, the sheet thickness is not more than 0.50 mm and the {411}<011> random intensity ratio at a 1 / 2 sheet thickness part is not less than 4.0.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a non-oriented electrical steel sheet. [Background technology]

[0002] Non-oriented electrical steel sheets are used, for example, in the iron cores of motors, and are required to have excellent magnetic properties, such as low core loss and high magnetic flux density, in the average of all directions parallel to the sheet surface (hereinafter sometimes referred to as "all-around average (all-directional average) within the sheet surface"). Although various technologies have been proposed so far, it is difficult to obtain sufficient magnetic properties in all directions within the sheet surface. For example, even if sufficient magnetic properties can be obtained in a certain direction within the sheet surface, sufficient magnetic properties may not be obtained in other directions.

[0003] It is well known that the development of {100} crystal orientation or the reduction of {111} crystal orientation is effective in improving magnetic properties. In order to control such crystal orientation, various studies have been conducted on component systems in which γ→α phase transformation occurs, as shown in Patent Documents 1 to 6. One of the key points in these technologies is to refine the hot-rolled structure. By using a steel composition with a low γ→α phase transformation temperature, accumulating a large amount of strain in the γ phase by low-temperature γ region hot rolling, and then transforming from there, a fine-grained α phase structure is realized at the time of hot-rolling. To achieve this, the addition of γ-stabilizing elements such as Mn, Cu, and Ni is utilized from the viewpoint of lowering the transformation temperature and delaying recovery recrystallization to promote the accumulation of strain. However, Mn is known as a segregation element, and if the content increases, it segregates in the center of the hot-rolled sheet and causes cracks when the hot-rolled sheet is cold-rolled. In addition, the technology that utilizes the γ→α phase transformation is being developed. <011> Since orientation is the main issue, in-plane anisotropy is large, and a new type of crystal orientation control is required. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Patent No. 4029430 [Patent Document 2] Patent No. 6319465 [Patent Document 3] JP 2017-193731 A [Patent Document 4] WO2021 / 095846 [Patent Document 5] Patent Publication No. 2021-080501 [Patent Document 6] JP 2020-100860 A Summary of the Invention [Problem to be solved by the invention]

[0005] In view of the above-mentioned problems, the present disclosure aims to provide a non-oriented electrical steel sheet having a chemical composition in which Mn is suppressed so as to prevent rollability from becoming an issue, and the contents of elements such as Mn, Cu and Ni are optimized, and which is capable of obtaining magnetic properties with small in-plane anisotropy and excellent circumferential average (all-directional average). [Means for solving the problem]

[0006] (1) A non-oriented electrical steel sheet according to one embodiment of the present disclosure, In mass%, C: 0.0100% or less, Si: 1.50%~4.00%, Sol.Al: 0.0001%~1.0%, S: 0.0100% or less, N: 0.0100% or less, Mn: 0.10% or more, One or more selected from Mn, Ni, and Cu: less than 2.50% in total; Mo: 0.00% to less than 2.50% Cr: 0.00% to less than 2.50%, Ti: 0.000%~0.005%, Nb: 0.000%~0.005%, Sn: 0.000%~0.400%, Sb: 0.000%~0.400%, P: 0.000% to 0.400%, and One or more selected from the group consisting of Mg, Ca, Sr, Ba, Ce, La, Nd, Pr, Zn, and Cd: 0.0000% to 0.0100% in total; The alloy has a chemical composition in which the transformation temperature Ar3 (°C) defined by the following formula (1) is 750 to 1050°C, with the balance being Fe and impurities, where the C content is [C], the Mo content is [Mo], the Cr content is [Cr], the Mn content is [Mn], the Ni content is [Ni], the Cu content is [Cu], the Si content is [Si], the sol.Al content is [sol.Al], and the P content is [P], in mass%, And the plate thickness is 0.50 mm or less, {411} at 1 / 2 thickness <011> The random intensity ratio is 4.0 or more. Ar3(℃)=1020-325×[C]+33×[Si]+287×[P]+80×[sol.Al]-120×([Mn]+[Mo]+[Cu])-46×([Cr]+[Ni]) ···(1)

[0007] (2) A non-oriented electrical steel sheet according to one embodiment of the present disclosure, In mass%, C: 0.0100% or less, Si: 1.50%~4.00%, Sol.Al: 0.0001%~1.0%, S: 0.0100% or less, N: 0.0100% or less, Mn: 0.10% or more, One or more selected from Mn, Ni, Co, Pt, Pb, Au, and Cu: less than 2.50% in total; Mo: 0.00% to less than 2.50% Cr: 0.00% to less than 2.50%, Ti: 0.000%~0.005%, Nb: 0.000%~0.005%, Sn: 0.000%~0.400%, Sb: 0.000%~0.400%, P: 0.000% to 0.400%, and One or more selected from the group consisting of Mg, Ca, Sr, Ba, Ce, La, Nd, Pr, Zn, and Cd: 0.0000% to 0.0100% in total; The alloy has a chemical composition in which the transformation temperature Ar3 (°C) defined by the following formula (1) is 750 to 1050°C, with the balance being Fe and impurities, where the C content is [C], the Mo content is [Mo], the Cr content is [Cr], the Mn content is [Mn], the Ni content is [Ni], the Cu content is [Cu], the Si content is [Si], the sol.Al content is [sol.Al], and the P content is [P], in mass%, And the plate thickness is 0.50 mm or less, {411} at 1 / 2 thickness <011> A non-oriented electrical steel sheet having a random strength ratio of 4.0 or more. Ar3(℃)=1020-325×[C]+33×[Si]+287×[P]+80× [sol.Al]-120×([Mn]+[Mo]+[Cu])-46×([Cr]+[Ni]) ···(1) (3) In the non-oriented electrical steel sheet according to (1) or (2), Magnetic flux density B at 45° to the rolling direction 50 may be 1.75T or more. (4) In the non-oriented electrical steel sheet described in (3) above, The value of magnetic flux density B50 in the rolling direction is B 50L , magnetic flux density B at 45° to the rolling direction 50 The value of B 50D , magnetic flux density B at 90° to the rolling direction 50 The value of B 50C Then, the following formula (2) may be satisfied. |B 50D -(B 50L +B 50C ) / 2|≦0.3 (2) Effect of the Invention

[0008] According to the above-described aspects of the present disclosure, it is possible to provide a non-oriented electrical steel sheet having a chemical composition in which Mn is suppressed so as to prevent rollability from becoming an issue, and the contents of elements such as Mn, Cu, and Ni are optimized, and which has small in-plane anisotropy and excellent magnetic properties averaged all around (averaged in all directions). [Brief description of the drawings]

[0009] [Figure 1] FIG. 1 shows an ODF of a φ2=45° cross section in which an example of the crystal orientation of the present disclosure is displayed. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The present inventors have conducted extensive research to solve the above problems. As a result, it has been found that the amount of Mn added is kept low to ensure rollability, and the composition is further adjusted. The hot rolling conditions are then optimized to form an appropriate α-deformed grain structure at the hot rolled sheet stage, and the {411} phase at the 1 / 2 sheet thickness portion can be improved by subsequent cold rolling and intermediate annealing. <011> This {411} <011> The grain orientation is further enriched by strain-induced grain boundary migration (SIBM) during the final annealing of the intermediate annealed sheet, which is then skin-pass rolled. <011> It became clear that enriching the magnetic properties was effective in reducing the in-plane anisotropy of the magnetic properties and improving the circumferential average (all-directional average).

[0011] Based on these findings, the present inventors conducted further intensive research and arrived at the present disclosure.

[0012] Hereinafter, the embodiments of the present disclosure will be described in detail. In this specification, a numerical range expressed using "~" means a range including the numerical values ​​before and after "~" as the lower and upper limits. It is also self-evident that each element of the following embodiments can be combined with each other. Furthermore, in the embodiments of the present disclosure, "non-oriented electrical steel sheet" refers not only to coil-shaped or cut-plate steel sheets, but also to steel sheets processed into specific shapes as materials for products (components) such as motor cores, and further to steel sheets that are laminated after processing to form motor cores.

[0013] First, the chemical composition of the non-oriented electrical steel sheet according to the embodiment of the present disclosure and the steel material used in the manufacturing method thereof will be described. In the following description, the unit of content of each element contained in the non-oriented electrical steel sheet or steel material, "%", means "mass %" unless otherwise specified. In addition, the chemical composition of the non-oriented electrical steel sheet indicates the content when the base material excluding the coating, etc. is taken as 100%. In addition, in the numerical ranges described in stages in this specification, the upper limit value of a certain numerical range may be replaced by the upper limit value of another numerical range described in stages, or may be replaced by a value shown in the examples. In the numerical ranges described in stages in this specification, the lower limit value of a certain numerical range may be replaced by the lower limit value of another numerical range described in stages, or may be replaced by a value shown in the examples.

[0014] The non-oriented electrical steel sheet according to this embodiment has a chemical composition in which ferrite-austenite transformation (hereinafter, α-γ transformation) can occur, In mass%, C: 0.0100% or less, Si: 1.50%~4.00%, Sol.Al: 0.0001%~1.0%, S: 0.0100% or less, N: 0.0100% or less, Mn: 0.10% or more, One or more selected from Mn, Ni, and Cu: less than 2.50% in total; Mo: 0.00% to less than 2.50% Cr: 0.00% to less than 2.50% Ti: 0.000% to 0.005% Nb: 0.000% to 0.005% Sn: 0.000%~0.400%, Sb: 0.000%~0.400%, P: 0.000% to 0.400%, and The alloy has a chemical composition comprising one or more elements selected from the group consisting of Mg, Ca, Sr, Ba, Ce, La, Nd, Pr, Zn, and Cd: 0.0000% to 0.0100% in total, with the contents of C, Si, P, sol. Al, Mn, Mo, Cu, Cr, and Ni satisfying the specified conditions described below, and the balance being Fe and impurities.

[0015] In the non-oriented electrical steel sheet according to this embodiment, one or more elements selected from Mn, Ni, Co, Pt, Pb, Au, and Cu are preferably contained in a total amount of less than 2.50%.

[0016] Examples of impurities include those contained in raw materials such as ores and scraps, and those contained in the manufacturing process.

[0017] (C: 0.0100% or less) C increases iron loss and causes magnetic aging. Therefore, the lower the C content, the better. This phenomenon is prominent when the C content exceeds 0.0100%. For this reason, the C content is set to 0.0100% or less. Reducing the C content also contributes to uniformly improving the magnetic properties in all directions within the plate surface. There is no particular lower limit for the C content, but it is preferably set to 0.0005% or more, taking into account the cost of decarburization during refining.

[0018] (Si: 1.50% to 4.00%) Silicon increases electrical resistance, reduces eddy current loss, reduces iron loss, and increases the yield ratio to improve punching workability into iron cores. If the Si content is less than 1.50%, these effects cannot be fully obtained. Therefore, the Si content is set to 1.50% or more. On the other hand, if the Si content exceeds 4.00%, the magnetic flux density decreases, punching workability decreases due to an excessive increase in hardness, and cold rolling becomes difficult. Therefore, the Si content is set to 4.00% or less.

[0019] (sol.Al:0.0001%~1.0%) Sol.Al increases electrical resistance, reduces eddy current loss, and reduces iron loss. Sol.Al reduces the magnetic flux density B 50 It also contributes to improving the relative size of the sol.Al. If the sol.Al content is less than 0.0001%, these effects cannot be fully obtained. Furthermore, Al also has the effect of promoting desulfurization during steelmaking. Therefore, the sol.Al content is set to 0.0001% or more. On the other hand, if the sol.Al content exceeds 1.0%, the magnetic flux density decreases and the yield ratio decreases, resulting in a decrease in punching workability. Therefore, the sol.Al content is set to 1.0% or less. Incidentally, sol. Al means acid-soluble Al that is not in the form of an oxide such as Al2O3 and is soluble in acid.

[0020] Here, the magnetic flux density B 50 is the magnetic flux density in a magnetic field of 5000 A / m.

[0021] (S:0.0100% or less) S is not an essential element, and is contained, for example, as an impurity in steel. S inhibits recrystallization and grain growth during annealing by precipitating fine MnS. Therefore, the lower the S content, the better. Such an increase in iron loss and a decrease in magnetic flux density due to the inhibition of recrystallization and grain growth are significant when the S content exceeds 0.0100%. For this reason, the S content is set to 0.0100% or less. There is no particular lower limit for the S content, but it is preferably set to 0.0003% or more in consideration of the cost of desulfurization treatment during refining.

[0022] (N:0.0100% or less) Like C, N deteriorates magnetic properties, so the lower the N content, the better. Therefore, the N content is set to 0.0100% or less. There is no particular lower limit for the N content, but it is preferably set to 0.0010% or more in consideration of the cost of denitrification treatment during refining.

[0023] (One or more selected from Mn, Ni, and Cu: less than 2.50% in total) If the total content of Mn, Ni, and Cu is 2.5% or more, the anisotropy of the magnetic properties increases, so the total content of Mn, Ni, and Cu is less than 2.5%. The reason why the anisotropy increases is not clear, but it is thought to be because it affects slip deformation in the ferrite region and promotes the formation of the {100} orientation and recrystallization. From this point of view, it is preferable that the increase in the content of the alloying elements is 2.3% or less. The lower limit of the total content of Mn, Ni, and Cu is not particularly limited, but may be, for example, 0.10% or more, 0.50% or more, 1.00% or more, or even 2.00% or more.

[0024] (One or more selected from Mn, Ni, Co, Pt, Pb, Au, and Cu: less than 2.50% in total) In addition to the above-mentioned Mn, Ni, and Cu, Co, Pt, Pb, and Au also increase the anisotropy of the magnetic properties, so in this embodiment, it is preferable to keep the total content of these elements below 2.50%. Also, since these elements reduce the magnetic flux density, it is preferable to keep the total content below 2.00%. The lower limit of the total content of Mn, Ni, Co, Pt, Pb, Au, and Cu is not particularly limited, but may be, for example, 0.10% or more, 0.50% or more, 1.00% or more, or even 2.00% or more. In particular, Co, Pt, Pb, and Au are expensive alloys, so their active addition should be avoided. Also, considering the control of the Ar3 transformation point, which is one of the features of this embodiment, it is preferable to control the Ar3 transformation point by including Mn, Ni, and Cu. For this reason, the total amount of Co, Pt, Pb, and Au is less than 0.5%, more preferably 0.1% or less, and furthermore, the inclusion is limited to the range of unavoidable elements, and there is no need to actively add them (it may be 0%).

[0025] Furthermore, the non-oriented electrical steel sheet and steel material according to the present embodiment further satisfy the following condition as a condition under which the α-γ transformation can occur: That is, when the C content is [C], the Mo content is [Mo], the Cr content is [Cr], the Mn content is [Mn], the Ni content is [Ni], the Cu content is [Cu], the Si content is [Si], the sol.Al content is [sol.Al], and the P content is [P], in mass%, the transformation temperature Ar3 (°C) defined by the following formula (1) is 750 to 1050°C.

[0026] Ar3(℃)=1020-325×[C]+33×[Si]+287×[P]+80×[sol.Al]-120×([Mn]+[Mo]+[Cu])-46×([Cr]+[Ni]) ···(1)

[0027] If the above formula (1) is not satisfied, even if the α-γ transformation occurs, the transformation point is not in the appropriate temperature range, so sufficient magnetic flux density cannot be obtained even if the manufacturing method described below is applied. If the Ar3 transformation point is less than 750°C, the hot rolling temperature becomes low, so the deformation resistance increases and the load on the rolling mill becomes too large, and the amount of added elements increases, which leads to a decrease in toughness of the hot-rolled sheet and cold-rolled sheet, so this value is set as the lower limit. On the other hand, if the Ar3 transformation point exceeds 1050°C, the hot rolling temperature becomes too high, so extremely high temperature heating is required, which increases the load on the heating furnace, or the composition system does not cause γ→α transformation, so this value is set as the upper limit.

[0028] (Mn: 0.10% or more, the total of one or more selected from Mn, Ni, and Cu, or the total of one or more selected from Mn, Ni, Co, Pt, Pb, Au, and Cu is less than 2.5%) Mn lowers the Ar3 transformation point, and in the component system of the non-oriented electrical steel sheet according to this embodiment, it enables the refinement of crystal grains of the hot-rolled sheet by phase transformation. Mn is an element that increases the electrical resistance of steel and reduces iron loss. Therefore, Mn is contained at 0.10% or more. From this viewpoint, Mn is preferably contained at 0.50% or more. More preferably, it is contained at 1.00% or more. On the other hand, Mn is an element that easily segregates, and if the content increases, not only does it cause cold work cracks due to segregation, but it also reduces the saturation magnetic flux density and prevents an increase in the magnetic flux density of the steel sheet. In addition, MnS is excessively generated, and the cold workability is reduced. Therefore, the upper limit of the Mn content is limited to less than 2.5%. Specifically, the upper limit of the Mn content is preferably 2.3 mass% or less, and more preferably 2.0 mass% or less.

[0029] (Cu: The total amount of one or more selected from Mn, Ni, and Cu, or the total amount of one or more selected from Mn, Ni, Co, Pt, Pb, Au, and Cu is less than 2.5%.) Cu, like Mn, is an element that increases the electrical resistance of the steel sheet and reduces iron loss, and is an element that lowers the Ar3 transformation point and enables the refinement of the grain size of the hot-rolled sheet by phase transformation in the chemical composition of the non-oriented electrical steel sheet according to this embodiment. However, if the Cu content is high, it not only has a negative effect on the formation of texture in annealing after cold rolling due to an increase in recrystallization temperature, and causes embrittlement in the hot state, but also reduces the saturation magnetic flux density and prevents the magnetic flux density of the steel sheet from increasing, so caution is required. Therefore, the Cu content is limited to less than 2.5%. In addition, by adding Ni in an amount equal to or more than half the Cu content, embrittlement in the hot state caused by Cu can be reduced. Specifically, the upper limit of the Cu content is preferably 1.5% by mass or less, and more preferably 1.0% by mass or less. The lower limit of the Cu content is not particularly limited, but may be, for example, 0.01% or more.

[0030] (Ni: The total content of one or more selected from Mn, Ni, and Cu, or the total content of one or more selected from Mn, Ni, Co, Pt, Pb, Au, and Cu is less than 2.5%) Ni, like Mn, increases the electrical resistance of the steel sheet and reduces iron loss. Ni further lowers the Ar3 transformation point, enabling the crystal grains to be refined by phase transformation in the chemical composition of the non-oriented electrical steel sheet according to this embodiment. However, if the Ni content is too high, not only will the product cost increase because Ni is expensive, but it will also reduce the saturation magnetic flux density and prevent an increase in the magnetic flux density of the steel sheet, so it is preferable to take these factors into consideration when designing the content. Therefore, the Ni content is limited to less than 2.5%. Specifically, the upper limit of the Ni content is preferably 1.0 mass% or less, and more preferably 0.7 mass% or less. The lower limit of the Ni content is not particularly limited and may be 0%, but may be, for example, 0.01% or more.

[0031] (Mo: 0.00% to less than 2.50%) Mo is an element that lowers the Ar3 transformation point and enables the grain size of the hot-rolled sheet to be refined by phase transformation in the chemical composition of the non-oriented electrical steel sheet according to this embodiment. Therefore, Mo may be added as necessary, and it is preferable to add 0.10% or more. On the other hand, since adding 2.50% or more of Mo significantly reduces the cold workability, the Mo content is set to less than 2.50%.

[0032] (Cr: 0.00% to less than 2.50%) Cr is an element that lowers the Ar3 transformation point and enables the grain size of the hot-rolled sheet to be refined by phase transformation in the chemical composition of the non-oriented electrical steel sheet according to this embodiment, and has the effect of improving not only strength adjustment and corrosion resistance, but also high-frequency characteristics in particular. Therefore, Cr may be contained as necessary, and it is preferable to contain 0.10% or more. On the other hand, excessive Cr content not only saturates the effect and increases the raw material cost, but also reduces the saturation magnetic flux density and prevents an increase in the magnetic flux density of the steel sheet. For this reason, the Cr content is set to less than 2.50%.

[0033] (Ti: 0.000%~0.005%) Ti, when present as a solid solution or TiN, inhibits recrystallization and contributes to refinement of the austenite grain size. Therefore, Ti may be added as necessary, and it is preferable to add 0.001% or more. On the other hand, if the Ti content exceeds 0.005%, various precipitates such as TiN, TiS, and TiC are generated, which deteriorates the iron loss characteristics, so the Ti content is set to 0.005% or less.

[0034] (Nb: 0.000%~0.005%) Nb, when present in the form of solid solution or NbN, inhibits recrystallization and contributes to refinement of the austenite grain size. Therefore, Nb may be added as necessary, and it is preferable to add 0.001% or more. On the other hand, if the Nb content exceeds 0.005%, various precipitates such as NbN and NbC are generated, which deteriorates the iron loss characteristics, so the content is set to 0.005% or less.

[0035] (Sn:0.000%~0.400%, Sb:0.000%~0.400%, P:0.000%~0.400%) Sn and Sb improve the texture after cold rolling and recrystallization, and increase the magnetic flux density. Therefore, these elements may be added as necessary, but if they are included in excess, they embrittle the steel. Therefore, the Sn content and Sb content are both set to 0.400% or less. Furthermore, P may be added to ensure the hardness of the steel sheet after recrystallization, but if it is included in excess, it will embrittle the steel. Therefore, the P content is set to 0.400% or less.

[0036] In order to impart further effects such as magnetic properties, it is preferable to contain one or more elements selected from the group consisting of 0.020% to 0.400% Sn, 0.020% to 0.400% Sb, and 0.020% to 0.400% P.

[0037] (One or more selected from the group consisting of Mg, Ca, Sr, Ba, Ce, La, Nd, Pr, Zn, and Cd: 0.0000% to 0.0100% in total) Mg, Ca, Sr, Ba, Ce, La, Nd, Pr, Zn and Cd react with S in the molten steel during casting of the molten steel to form precipitates of sulfides or oxysulfides, or both. Hereinafter, Mg, Ca, Sr, Ba, Ce, La, Nd, Pr, Zn and Cd may be collectively referred to as "coarse precipitate forming elements". The particle size of the precipitates of the coarse precipitate forming elements is about 1 μm to 2 μm, which is much larger than the particle size (about 100 nm) of fine precipitates such as MnS, TiN, AlN, TiC, NbC, etc. For this reason, these fine precipitates adhere to the precipitates of the coarse precipitate forming elements, and are less likely to inhibit recrystallization and grain growth during annealing such as intermediate annealing. In order to fully obtain these effects, it is preferable that the total amount of the coarse precipitate forming elements is 0.0005% or more. However, if the total content of these elements exceeds 0.0100%, the total amount of sulfides or oxysulfides or both will be excessive, which will inhibit recrystallization and grain growth during annealing such as intermediate annealing. Therefore, the total content of the elements that form coarse precipitates is set to 0.0100% or less.

[0038] In this embodiment, the balance of the chemical composition other than the above may be Fe and impurities. The impurities refer to elements that are mixed in the steel raw materials and / or during the steelmaking process. do.

[0039] The chemical composition is determined by the following method. The chemical composition can be measured by a general analysis method for steel. For example, the chemical composition can be measured using ICP-AES (Inductively Coupled Plasma-Atomic Emission Spectrometry). Specifically, the chemical composition can be determined by measuring test pieces taken from the steel plate with a specified measuring device under conditions based on a previously prepared calibration curve. C and S can be measured using the combustion-infrared absorption method, and N can be measured using the inert gas fusion-thermal conductivity method. O can be measured using the inert gas fusion-non-dispersive infrared absorption method. If the surface has an insulating coating, it may be mechanically removed using a minitor or the like before being subjected to analysis.

[0040] Next, the metal structure of the non-oriented electrical steel sheet according to this embodiment will be described. Although the details of the manufacturing method will be described later, the non-oriented electrical steel sheet according to this embodiment has a chemical composition in which α-γ transformation can occur.

[0041] Next, the thickness of the non-oriented electrical steel sheet according to this embodiment will be described. The thickness of the non-oriented electrical steel sheet according to this embodiment is 0.50 mm or less. The preferred thickness of the non-oriented electrical steel sheet according to this embodiment is 0.10 to 0.50 mm. Usually, as the thickness decreases, the iron loss decreases, but the magnetic flux density decreases. In view of this, if the thickness is 0.10 mm or more, the iron loss is lower and the magnetic flux density is higher. Furthermore, if the thickness is 0.50 mm or less, low iron loss can be maintained. The lower limit of the thickness is more preferably 0.20 mm, and even more preferably 0.30 mm.

[0042] In addition, the non-oriented electrical steel sheet according to the present embodiment has a {411} <011> The random intensity ratio is 4.0 or more. {411} at 1 / 2 thickness <011> The random strength ratio is the "random strength ratio" of the non-oriented electrical steel sheet after final annealing. {411} at 1 / 2 thickness <011> If the random intensity ratio is less than 4.0, crystal grains having a {111} plane orientation will develop after the final annealing, making it impossible to obtain sufficient magnetic properties. {411} at 1 / 2 thickness <011> The upper limit of the random intensity ratio is not particularly limited, but is, for example, 30.0 or less. In addition, the {411} <148> When the random intensity ratio is 5.0 or more, {411} <148> Due to the well-developed orientation, the {411} <011> The random intensity ratio does not satisfy 4.0 or more. In the following, unless otherwise specified, "{411} at 1 / 2 thickness" is used. <011> "Random Intensity Ratio of {411} <011> This is also called the "random intensity ratio of

[0043] The random intensity ratio generally means the ratio to the X-ray integrated intensity of a sample in which the accumulation state of the crystal orientation is random. The X-ray intensity of a standard sample and a test material that do not have accumulation in a specific orientation is measured under the same conditions by X-ray diffraction method or the like, and the value is obtained by dividing the X-ray intensity of the test material obtained by the X-ray intensity of the standard sample. It can be obtained from a crystal orientation distribution function (referred to as ODF) that represents a three-dimensional texture, calculated by a series expansion method based on multiple pole figures among {110}, {100}, {211}, and {310} pole figures measured by X-ray diffraction. On the other hand, a similar ODF can also be obtained from crystal orientation data obtained by measurement using EBSD (Electron Back Scattering Diffraction), so the value of the random intensity ratio in this disclosure is a value measured using EBSD as follows. FIG. 1 shows an ODF of a φ2=45° cross section showing an example of the crystal orientation of the present disclosure. <011> is expressed as a point at φ1 = 0°, Φ = 20°, but since measurement errors may occur due to test piece processing and sample setting, it is expressed as the maximum value within the range of φ1 = 0 to 5°, Φ = 15 to 25°, shown by the shaded area in the figure. In addition, since ODF is also used to display the orientation of a crystal structure with low symmetry, it is generally expressed as φ1=0 to 360°, Φ=0 to 180°, and φ2=0 to 360°, and each orientation is displayed as (hkl)[uvw]. However, since the present disclosure targets a bcc crystal structure with high symmetry, Φ and φ2 are expressed in the range of 0 to 90°. In addition, the range of φ1 changes depending on whether or not symmetry due to deformation is considered when performing calculations, but in the present disclosure, it is expressed as φ1=0 to 90° in consideration of symmetry. That is, a method is selected in which the average value of the same orientation at φ1=0 to 360° is displayed on the ODF of 0 to 90°. Next, the measurement conditions for EBSD are described. The steel plate is polished to a specified position in the plate thickness direction by mechanical polishing or chemical polishing, and then finished to a mirror finish by buffing. After that, distortion is removed by electrolytic polishing or chemical polishing, and the measurement surface is adjusted so that the 1 / 2 plate thickness part becomes the measurement surface. Note that it is difficult to precisely position the measurement surface at the specified plate thickness position, so it is sufficient to prepare the sample so that the measurement surface is within a range of 3% of the plate thickness, centered on the target position. The measurement range is 1 mm or more in both the rolling direction and the rolling width direction. There are no particular regulations regarding the measurement interval, but it is desirable to adjust it so that the number of measurement points is 50,000 or more. The detailed conditions for creating ODF from data obtained by EBSD using the analysis software OIM Analysis by EDAX / TSL are shown below. Series Rank(L):16 ·Gaussian Half-Width[degrees]:5 ·Sample Symmetry: Orthotropic(Rolled sheet) ·Bunge Euler Angles: φ1=0~90°, φ=0~90°, φ2=45°

[0044] Next, the magnetic properties of the non-oriented electrical steel sheet according to this embodiment will be described. The non-oriented electrical steel sheet according to this embodiment has the best magnetic properties in the 45° direction among the three directions that form angles of 0°, 45°, and 90° with the rolling direction. In this embodiment, the angle with the rolling direction refers to the angle with the rolling direction within the sheet surface. In this embodiment, the magnetic properties in the 45° direction are the average value of the magnetic properties in two directions that form angles of +45° and -45° with the rolling direction.

[0045] When the magnetic flux density of the non-oriented electrical steel sheet according to this embodiment was measured, the magnetic flux density B 50 is preferably 1.75 T or more. In the non-oriented electrical steel sheet according to this embodiment, the magnetic flux density is high in the direction at 45° to the rolling direction, the in-plane anisotropy is small, and a high magnetic flux density can be obtained even on the circumferential average (all-directional average).

[0046] In the non-oriented electrical steel sheet according to this embodiment, the magnetic flux density B 50 The value of B 50L , magnetic flux density B at 45° to the rolling direction 50 The value of B 50D , magnetic flux density B at 90° to the rolling direction 50 The value of B 50C Then, B 50D is relatively high, B 50L and B. 50C The magnetic flux density is anisotropic, with the

[0047] In the non-oriented electrical steel sheet according to this embodiment, B 50D And B 50L and B 50C It is more preferable to satisfy the following formula (2) using the average value of

[0048] |B 50D -(B 50L +B 50C ) / 2|≦0.3 (2)

[0049] Moreover, the value on the left side of the above formula (2) is preferably 0.2 or less, and more preferably 0.1 or less. There is no particular lower limit to the value on the left side of the above formula (2), but it is preferably zero.

[0050] The magnetic flux density can be measured by cutting a 55 mm square sample from a direction at 45° or 0° to the rolling direction, and using a single sheet magnetic measurement device.

[0051] Next, an example of a method for producing the non-oriented electrical steel sheet according to the present embodiment will be described. The non-oriented electrical steel sheet according to the present embodiment is obtained by a production method including a hot rolling step, a cold rolling step, an intermediate annealing step, a skin pass rolling step, and a final annealing step. Preferred conditions for each step will now be described. Hereinafter, in this embodiment, the Ar3 temperature is the transformation temperature Ar3 (° C.) defined by the above formula (1).

[0052] (Hot rolling process) In the hot rolling process, hot rolling is performed on the steel material satisfying the above-mentioned chemical composition to produce a hot rolled steel sheet. The hot rolling process includes a heating process and a rolling process.

[0053] The steel material is, for example, a slab produced by normal continuous casting, and the steel material having the above-mentioned composition is produced by a known method. For example, molten steel is produced in a converter or electric furnace. The produced molten steel is subjected to secondary refining in a degassing facility or the like to produce molten steel having the above-mentioned chemical composition (the chemical composition does not change substantially in the subsequent steps). The molten steel is cast into a slab by a continuous casting method or an ingot casting method. The cast slab may be subjected to blooming rolling.

[0054] In the heating process, it is preferable to heat the steel material having the above-mentioned chemical composition to 1000 to 1200° C. Specifically, the steel material is charged into a heating furnace or a soaking furnace and heated in the furnace. The holding time at the above heating temperature in the heating furnace or the soaking furnace is not particularly limited, but is, for example, 30 to 200 hours.

[0055] In the rolling process, the steel material heated in the heating process is rolled in multiple passes to produce a hot-rolled steel sheet. Here, "pass" means that the steel sheet passes through one rolling stand having a pair of work rolls and is subjected to rolling reduction. For example, hot rolling may be performed by tandem rolling using a tandem rolling mill including multiple rolling stands arranged in a row (each rolling stand having a pair of work rolls) to perform multiple passes, or by reverse rolling using a pair of work rolls to perform multiple passes. From the viewpoint of productivity, it is preferable to perform multiple rolling passes using a tandem rolling mill.

[0056] In the rolling process (rough rolling and finish rolling), the above-mentioned steel material is heated and hot-rolled. The steel material is, for example, a slab manufactured by normal continuous casting. The slab is heated to the Ar3 temperature or higher, which is a temperature range in which the steel structure becomes a γ phase. Hot rolling is started in a temperature range in which the steel structure becomes a γ phase (hereinafter, this temperature range may be referred to as the γ range), and is performed in the γ range except for a necessary number of passes including the final pass of the finish rolling, and is completed by performing a necessary number of passes including the final pass in a temperature range in which the α phase exists in the steel structure (hereinafter, this temperature range may be referred to as the α range). In general, the front to middle stages of rough rolling and finish rolling are performed in the γ range, and the rear stage of finish rolling is performed in the α range. In this embodiment, the reduction rate in the temperature range from the Ar3 temperature to Ar3+20°C just before the final rolling in the α range is 10% or more. Furthermore, the reduction ratio in the temperature range of the finish rolling temperature FT or higher and lower than the Ar3 temperature is set to 15% or more in total, taking into consideration the case where rolling is performed in multiple passes. The finish rolling temperature FT refers to the surface temperature of the hot-rolled steel sheet immediately after finish rolling. The lower limit of the finish rolling temperature FT is not particularly limited, but is set to, for example, Ar3 temperature -100°C or more.

[0057] Rolling at temperatures above Ar3+20°C just before the final rolling in the α region has almost no effect on the grain size of the deformed γ grains before the phase transformation, but coarse deformed α grains are formed after the transformation, resulting in the {411} <011> This is unrelated to the concentration in the If the rolling reduction ratio in the temperature range between Ar3 and Ar3+20°C immediately before the final rolling in the α region is less than 10%, the accumulation of strain in the deformed γ grains before the phase transformation is insufficient, resulting in the formation of coarse deformed α grains, and the {411} <011> The rolling reduction in the temperature range of Ar3 temperature or higher and Ar3+20°C or lower is preferably 15% or higher, more preferably 20% or higher. Although there is no upper limit for the total rolling reduction, a reduction of more than 40% places too much strain on the rolling mill, so the upper limit is preferably set at 40%. If the total reduction rate in the temperature range between the final finish rolling temperature FT and the Ar3 temperature in the final α region is less than 15%, the processed α grains after phase transformation from the processed γ grains cannot accumulate sufficient processing strain in the α region, and the {411} <011> Accumulation in the crystal orientation is less likely to occur. The rolling reduction in the temperature range of the finish rolling temperature FT or more and less than the Ar3 temperature is preferably 20% or more, more preferably 25% or more. There is no upper limit to the total rolling reduction, but a reduction exceeding 40% puts too much strain on the rolling mill, so it is preferable to set the upper limit at 40%. In this embodiment, the reduction ratio RR0 in the hot rolling is defined as follows. Reduction rate RR0 (%) = (1 - thickness after rolling in the relevant temperature range in hot rolling / thickness before rolling in the relevant temperature range in hot rolling) x 100

[0058] The lower limit temperature for rolling in the α region is not particularly limited, but since a lower rolling temperature increases the load on the rolling mill, it is preferable to set the lower limit temperature to 600° C. or higher. The rolling temperature may fluctuate above or below the specified judgment temperature (Ar3 temperature or Ar3+20°C) during the rolling pass due to the competition between the temperature drop caused by roll contact and cooling lubricant and the temperature rise caused by processing. In this embodiment, such a situation is handled as follows. In a rolling pass, it is assumed that the temperature at the entry side is TPI (℃), the thickness at the entry side is TCI (mm), the temperature at the exit side is TPO (℃), and the thickness at the exit side is TCO (mm), and furthermore that the thickness change and temperature change during the rolling pass change while maintaining a simple linear relationship. In other words, if the thickness at a specific point in time during a rolling pass is TCa (mm) and the temperature is TPa (℃), it is assumed that the following formula always holds true during the rolling pass. (TCa-TCO) / (TCI-TCO)=(TPa-TPO) / (TPI-TPO) This makes it possible to determine the plate thickness at that time point even when the prescribed judgment temperature in this manufacturing method (Ar3 temperature, or Ar3+20°C) is reached during a rolling pass. In other words, the plate thickness TCa (mm) when a specific temperature TPa (℃) is reached during the rolling pass is: TCa=TCO+(TCI-TCO)×(TPa-TPO) / (TPI-TPO) can be obtained by:

[0059] It should be noted that the above assumption also assumes that the exit temperature of the rolling pass will be higher than the entry temperature. In other words, even in a situation where a steel sheet whose entry temperature TPI of the pass is lower than the Ar3 temperature rises in temperature due to processing heat in the pass and is discharged at an exit temperature TPO of Ar3 temperature or higher, it is determined that the steel sheet has been rolled in the γ range (temperature range of Ar3 temperature or higher and Ar3+20°C or lower) required for the present disclosure in the latter half of the pass. It is also possible that the temperature fluctuations on either side of the Ar3 temperature may occur over multiple passes. In such a case, in this embodiment, the rolling conditions in the α region are for the "final rolling process in the α region". In addition, the rolling conditions in the γ region are for the "rolling process in the γ region immediately before the above-mentioned 'final rolling process in the α region'". In other words, when the rolling temperature after starting hot rolling in the γ region changes as follows: γ region (start of hot rolling) ⇒ α region 1 ⇒ γ region 1 ⇒ α region 2 ⇒ γ region 2 ⇒ α region 3 (end of hot rolling), if the α region 3 and γ region 2 meet the conditions of this embodiment, it is possible to obtain the disclosed steel sheet.

[0060] The rolling temperature in each pass can be measured, for example, by a thermometer installed at the entry or exit of the rolling stand that performs the reduction of the target pass. It is not necessary to install thermometers at the entry and exit of all rolling stands whose temperature range falls within the range disclosed herein, and the rolling temperature at intermediate rolling stands may be calculated from the actual temperatures of thermometers appropriately installed before and after them. Rather, in current hot rolling, control using such calculated temperatures is usually performed.

[0061] Thereafter, the hot-rolled steel sheet is coiled without being annealed. The temperature during coiling is preferably more than 250°C and not more than 600°C. By coiling the hot-rolled steel sheet after hot rolling at more than 250°C and not more than 600°C, the crystal structure before cold rolling can be refined, and the {411} sintered steel sheet with excellent magnetic properties can be obtained during bulging. <011> The winding temperature is more preferably 400°C to 500°C, and even more preferably 400°C to 480°C.

[0062] (Cold rolling process) In the cold rolling process, the hot rolled steel sheet after the cooling process is cold rolled to obtain a cold rolled steel sheet. Specifically, after hot rolling, the hot rolled steel sheet is pickled and then cold rolled. In the cold rolling, the reduction ratio is preferably 80% to 92%. Note that the higher the reduction ratio, the more likely it is that the {411} <011> Although crystal grains having a crystal orientation tend to grow, the sheet shape deteriorates and operation becomes difficult.

[0063] (Intermediate annealing process) In the intermediate annealing step, the cold rolled steel sheet is subjected to intermediate annealing. In this embodiment, the temperature of the intermediate annealing is controlled to 700°C or higher and lower than 900°C. If the temperature of the intermediate annealing is lower than 700°C, the growth of crystal grains is insufficient, and the {411} <011> Moreover, at temperatures above 900°C, the grains grow excessively, and even if skin pass rolling and final annealing are performed, the {411} <011> In addition, if the intermediate annealing temperature is too low and sufficient recrystallization does not occur, the {411} crystal orientation will not be uniform even after skin pass rolling and final annealing, which will be described later. <011> The growth of crystal grains having a crystal orientation is inhibited. Therefore, the temperature of the intermediate annealing is preferably 700°C or more and less than 900°C, and more preferably 700°C or more and 800°C or less. The temperatures described here are based on the assumption of continuous annealing, and the intermediate annealing time is preferably in the range of 5 to 120 seconds. This annealing temperature range and annealing time range are set so as to prevent the {411} <011> It is believed that the oriented grains grow appropriately by bulging, and the conditions are favorable for creating a state in which strain-induced grain growth is likely to occur by carrying out the skin-pass rolling and final annealing described below.

[0064] (Skin pass rolling process) In the skin pass rolling process, skin pass rolling is performed on the steel sheet after the intermediate annealing process. As described above, when skin pass rolling and annealing are performed in a state where {411}<011> is enriched by bulging, the crystal grains having the {411}<011> crystal orientation further grow. This is because, due to skin pass rolling, strain hardly accumulates in the crystal grains having the {411}<011> crystal orientation, while strain easily accumulates in the crystal grains belonging to the orientation group having the {111} plane orientation called γ-fiber such as {111}<112> and {111}<110>. Then, in the subsequent annealing, the crystal grains having the {411}<011> crystal orientation with less strain eat away these γ-fiber oriented grains with the strain difference as the driving force. This eating phenomenon occurring with the strain difference as the driving force is called strain-induced grain boundary migration (hereinafter referred to as SIBM). The rolling reduction rate of the skin pass rolling is preferably 5.0% to less than 20.0%. If the rolling reduction rate is less than 5%, the amount of strain is too small, so strain-induced grain boundary migration (hereinafter referred to as SIBM) does not occur in the subsequent annealing, and the crystal grains having the {411}<011> crystal orientation do not grow. On the other hand, if the rolling reduction rate is 20% or more, the amount of strain becomes too large, and recrystallization nucleation (hereinafter referred to as Nucleation) occurs in which new crystal grains are generated from among the crystal grains having the γ-fiber orientation. In this Nucleation, most of the generated grains have the crystal grains having the γ-fiber orientation, so the magnetic properties deteriorate. From the viewpoint of increasing the average magnetic flux density in the sheet plane and reducing the anisotropy, the rolling reduction rate of the skin pass rolling is more preferably 5% to 15%.

[0065] In addition, in the non-oriented electrical steel sheet, when it is desired to have the strain distribution described above, when the rolling reduction rate (%) in cold rolling is RR1 and the rolling reduction rate (%) in skin pass rolling is RR2, it is preferable to adjust the rolling reduction rates of cold rolling and skin pass rolling so that 71.0 < RR1 - RR2 < 75.0.

[0066] Here, the rolling reduction rate RR1 (%) in cold rolling is defined as follows. Rolling reduction rate RR1 (%) = (1 - thickness of the sheet after rolling in the final pass of cold rolling / thickness of the sheet before rolling in the first pass of cold rolling) × 100 The reduction ratio RR2 (%) in skin pass rolling is defined as follows. Reduction ratio RR2 (%) = (1 - thickness after the final pass of skin pass rolling / thickness before the first pass of skin pass rolling) x 100

[0067] (Final annealing process) In the final annealing step, the steel sheet after the skin-pass rolling is subjected to final annealing. This final annealing causes SIBM driven by the strain difference for each crystal orientation due to skin-pass rolling, and the {411} <011> The grains grow preferentially, and the {411} <011> The degree of orientation accumulation increases. The annealing conditions can be appropriately set by a person skilled in the art while checking the occurrence of SIBM, and are not particularly limited, but an example is annealing at 800°C for 2 hours. The annealing temperature may be, for example, 750°C to 900°C, 800°C to 900°C, or 850°C to 900°C.

[0068] As described above, the non-oriented electrical steel sheet according to this embodiment can be manufactured. This final annealing can be performed, for example, at a steel sheet manufacturer after skin pass rolling, in the form of a steel sheet coil or as a cut sheet. Alternatively, after skin pass rolling, the steel sheet can be shipped without final annealing, and the motor manufacturer can process the steel sheet into a predetermined shape as a motor core, laminate the steel sheet, and then perform the final annealing in the core shape. In the latter case, the final annealing can also be performed as a "stress relief annealing" that is generally performed on motor cores by motor manufacturers. If the steel sheet manufacturer performs the final annealing before shipping, motor manufacturers can use the disclosed steel sheet to obtain good motor characteristics. Also, if the steel sheet manufacturer ships the steel sheet up to skin pass rolling, and the motor manufacturer processes it into a motor core and then performs the final annealing as stress relief annealing, good motor characteristics can also be obtained using the disclosed steel sheet. The final annealing may be performed by both the steel sheet manufacturer and the motor manufacturer as a heat treatment two or more times. By adjusting the heat treatment after the skin pass, the amount of remaining strain, the grain size, and the {411} <011> The degree of orientation development can be adjusted. Steel sheets with a large amount of remaining strain or with a relatively small grain size are particularly suitable for use as non-oriented electrical steel sheets for rotor cores to suppress deformation due to centrifugal force accompanying the rotation of the core. On the other hand, steel sheets with sufficient strain release and coarse grain size are particularly suitable for use as non-oriented electrical steel sheets for stator cores to suppress iron loss.

[0069] The steel member made of the non-oriented electromagnetic steel sheet according to this embodiment is applied to, for example, the iron core (motor core) of a rotating electric machine. In this case, individual flat thin plates are cut out from the non-oriented electromagnetic steel sheet according to this embodiment, and these flat thin plates are appropriately laminated to produce the iron core used in the rotating electric machine. Since this iron core uses the non-oriented electromagnetic steel sheet with excellent magnetic properties, the iron loss is kept low, and a rotating electric machine with excellent torque is realized. The steel member made of the non-oriented electromagnetic steel sheet according to this embodiment can also be applied to products other than the iron core of a rotating electric machine, for example, the iron core of a linear motor or a stationary machine (reactor or transformer). It is possible. EXAMPLES

[0070] Next, the non-oriented electrical steel sheet according to the embodiment of the present disclosure will be specifically described with reference to examples. The examples shown below are merely examples of the non-oriented electrical steel sheet according to the embodiment of the present disclosure, and the non-oriented electrical steel sheet according to the present disclosure is not limited to the examples below.

[0071] The molten steel was cast to produce an ingot having the composition shown in Table 1. The "Co, etc." column in Table 1 indicates the content of Co, Pt, Pb, or Au. The produced ingot was then subjected to a hot rolling process, a cold rolling process, an intermediate rolling process, a skin pass rolling process, and a final annealing process under the conditions shown in Table 2. After the hot rolling, the hot rolled steel sheet was not annealed, and was coiled at a coiling temperature of 500°C. In the final annealing step, annealing was performed at the annealing temperature T2 shown in Table 2 for 2 hours. The following characteristics were then investigated using the method described above: Transformation temperature Ar3(℃) Plate thickness After final annealing, {411} <011> Random intensity ratio of Magnetic flux density B in the rolling direction 50L Magnetic flux density B at 45° to the rolling direction 50D Magnetic flux density B at 90° to the rolling direction 50C

[0072] The following evaluations were also carried out:

[0073] (Rollability) The rolling properties were evaluated as follows. In a 1m longitudinal area centered on a position 10m longitudinally from the outermost longitudinal tip of the cold-rolled sheet coil (top part), a position half the length of the coil's total length in the longitudinal direction from the outermost longitudinal tip of the coil (middle part), and a position 10m longitudinally from the innermost longitudinal tip of the coil (bottom part), if there were two or more cracks 1cm or more in length on both end faces in the sheet width direction of the coil, the rating was "N", otherwise "Y". In this embodiment, the cold-rolled coil was used as the evaluation target for rollability, but when evaluating a steel sheet cut out from a cold-rolled coil, both end faces in the sheet width direction may be observed in three or more different positions in the longitudinal direction (rolling direction) of the steel sheet in the same manner as described above. For example, the observation may be performed in a range of about 1 / 10 of the entire longitudinal length of the steel sheet, centered on positions of about 1 / 10, 1 / 2, and 9 / 10 of the longitudinal length of the steel sheet, and the entire longitudinal length of the steel sheet may be 1 m or more.

[0074] [Table 1-1]

[0075] [Table 1-2]

[0076] [Table 2-1]

[0077] [Table 2-2]

[0078] [Table 3-1]

[0079] [Table 3-2]

[0080] As can be seen from the above examples, the non-oriented electrical steel sheet according to the present disclosure has small in-plane anisotropy and excellent magnetic properties on an average around the circumference (average in all directions) by appropriately controlling the chemical composition, hot rolling conditions, cold rolling conditions, intermediate annealing conditions, skin pass rolling conditions, and final annealing process conditions. In addition, the rollability is also good.

[0081] In addition to the above examples, examples in which the hot rolling process, cold rolling process, intermediate rolling process, skin pass rolling process, and final annealing process were carried out under the conditions shown in Table 4 are also shown. In the following examples, in addition to the above characteristics and rollability, the following characteristics were also examined. After intermediate annealing and before skin pass, the {411} <011> Random strength ratio of After intermediate annealing and before skin pass, 1 / 8 thickness {411} <011> Random strength ratio of After final annealing, {411} at 1 / 8 thickness <011> Random strength ratio of

[0082] In addition, the {411} <011> The random strength ratio of the {411} <011> The random intensity ratio was measured in the same manner as above.

[0083] [Table 4-1]

[0084] [Table 4-2]

[0085] From the above examples, it can be seen that the non-oriented electrical steel sheet according to the present disclosure has small in-plane anisotropy and excellent magnetic properties on an average around the circumference (average in all directions) by appropriately controlling the chemical composition, hot rolling conditions, cold rolling conditions, intermediate annealing conditions, skin pass rolling conditions, and final annealing process conditions. In addition, the rollability is also good. In particular, in No. 36, the reduction ratios of cold rolling and skin pass rolling were low, and the {411} <011> The random strength ratio of {411} at the half thickness part after final annealing <011> It can be seen that both the random intensity ratios are low, and the magnetic properties are deteriorated. In addition, as shown in No. 37, the cold rolling reduction ratio and the difference RR1-RR2 are low, and the {411} <011> The random strength ratio of {411} at the half thickness part after final annealing <011> It can be seen that both the random intensity ratios are low, and the magnetic properties are deteriorated. These results also show that by appropriately controlling the cold rolling conditions and skin pass rolling conditions, the texture changes significantly during final annealing, improving the in-plane anisotropy and the circumferential average (all-directional average). [Industrial Applicability]

[0086] According to the present disclosure, it is possible to provide a non-oriented electrical steel sheet which has small in-plane anisotropy and can obtain excellent magnetic properties on average around the circumference (average in all directions), which is extremely useful industrially.

[0087] The disclosure of Japanese Patent Application No. 2023-001933 is incorporated herein by reference in its entirety. All publications, patent applications, and standards mentioned in this specification are herein incorporated by reference to the same extent as if each individual publication, patent application, or standard was specifically and individually indicated to be incorporated by reference.

Claims

1. In mass percent, C: 0.0100% or less, Si: 1.50% to 4.00%, sol. Al: 0.0001% to 1.0%, S: 0.0100% or less, N: 0.0100% or less, Mn: 0.10% or more, One or more selected from Mn, Ni, and Cu: less than 2.50% in total; Mo: 0.00% to less than 2.50% Cr: 0.00% to less than 2.50%; Ti: 0.000% to 0.005%, Nb: 0.000% to 0.005%, Sn: 0.000% to 0.400%, Sb: 0.000% to 0.400%, P: 0.000% to 0.400%, and One or more selected from the group consisting of Mg, Ca, Sr, Ba, Ce, La, Nd, Pr, Zn, and Cd: 0.0000% to 0.0100% in total; When the C content is [C], the Mo content is [Mo], the Cr content is [Cr], the Mn content is [Mn], the Ni content is [Ni], the Cu content is [Cu], the Si content is [Si], the sol. Al content is [sol. Al], and the P content is [P], the transformation temperature Ar is determined by the following formula (1). 3 (°C) is 750 to 1050°C, with the balance being Fe and impurities; And the plate thickness is 0.50 mm or less, A non-oriented electrical steel sheet having a {411}<011> random strength ratio of 4.0 or more at a 1 / 2 sheet thickness portion. Ar 3 (℃)=1020-325×[C]+33×[Si]+287×[P]+80×[sol.-]-120×([M]+[[[[[[])-46×([[[[[Ni]) ・・・(1)

2. In mass percent, C: 0.0100% or less, Si: 1.50% to 4.00%, sol. Al: 0.0001% to 1.0%, S: 0.0100% or less, N: 0.0100% or less, Mn: 0.10% or more, One or more selected from Mn, Ni, Co, Pt, Pb, Au, and Cu: less than 2.50% in total; Mo: 0.00% to less than 2.50% Cr: 0.00% to less than 2.50%; Ti: 0.000% to 0.005%, Nb: 0.000% to 0.005%, Sn: 0.000% to 0.400%, Sb: 0.000% to 0.400%, P: 0.000% to 0.400%, and One or more selected from the group consisting of Mg, Ca, Sr, Ba, Ce, La, Nd, Pr, Zn, and Cd: 0.0000% to 0.0100% in total; When the C content is [C], the Mo content is [Mo], the Cr content is [Cr], the Mn content is [Mn], the Ni content is [Ni], the Cu content is [Cu], the Si content is [Si], the sol. Al content is [sol. Al], and the P content is [P], the transformation temperature Ar is determined by the following formula (1). 3 (°C) is 750 to 1050°C, with the balance being Fe and impurities; And the plate thickness is 0.50 mm or less, A non-oriented electrical steel sheet having a {411}<011> random strength ratio of 4.0 or more at a 1 / 2 sheet thickness portion. Ar 3 (℃)=1020-325×[C]+33×[Si]+287×[P]+80×[sol.-]-120×([M]+[[[[[[])-46×([[[[[Ni]) ・・・(1)

3. Magnetic flux density B at 45° to the rolling direction 50 The non-oriented electrical steel sheet according to claim 1 or 2, wherein the hardness is 1.75T or more.

4. Magnetic flux density B in the rolling direction 50 The value of B 50L , magnetic flux density B in the direction at 45° to the rolling direction 50 The value of B 50D , magnetic flux density B in the direction 90° to the rolling direction 50 The value of B 50C The non-oriented electrical steel sheet according to claim 3, which satisfies the following formula (2): |B 50D -(B 50L +B 50C ) / 2|≦0.3・・・(2)

Citation Information

Patent Citations

  • Cam drive type traction type drive

    JP1988019465A

  • Non-oriented electromagnetic steel sheet and manufacturing method therefor

    JP2006219692A

  • Electromagnetic steel sheet, and method for producing the same

    JP2017193731A

  • Non-oriented electromagnetic steel sheet

    JP2020100860A

  • Non-oriented electromagnetic steel sheet

    JP2020139198A